2018
DOI: 10.1111/jai.13590
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of three common species of goatfish exploited by artisanal fishery in Hurghada fishing area, Egypt

Abstract: Summary The age and growth of three goatfish species Mulloidichthys flavolineatus (Lacepède, 1801), Mulloidichthys vanicolensis (Valenciennes, 1831) and Parupeneus forsskali (Fourmanoir & Guézé, 1976) from Egyptian Red Sea, Hurghada region were studied based on otolith readings. The fishing operated mainly by gill and tramml nets with mesh sizes renging from 0.5 to 3 cm. The maximum longevity of the three species was found to be 6, 5 and 5 years for M. flavolineatus, M. vanicolensis and P. forsskali respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Similar trends in length increment have been recorded for all previous studied fish species [e.g. 9,33,19,31,32,46].…”
Section: Discussionsupporting
confidence: 87%
“…Similar trends in length increment have been recorded for all previous studied fish species [e.g. 9,33,19,31,32,46].…”
Section: Discussionsupporting
confidence: 87%
“…The authors compared their results with those of previous studies and found that the Okinawan fish grew faster and larger than those in other waters (Table 2). This is because, based on the values of the von Bertalanffy growth parameters, the individuals from Okinawa were estimated to have faster initial growth than those from Aquba (Wahbeh, 1992) and Hurgada (Mehanna et al, 2018). The K value…”
Section: Life-history Traitsmentioning
confidence: 99%
“…An age assessment using scales and spawning season estimates using a gonado‐somatic index were reported in the Gulf of Aqaba (Red Sea) (Wahbeh, 1992). In Hurghada (Red Sea), an age analysis with mixed sexes was performed (Mehanna et al ., 2018). In Hawaii, a small sample of age assessments and spawning season estimates was reported (Cole, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overfishing situation was observed (Table 4) and agreed with all previous studies dealing with tstock assessment of Red Sea fisheries (eg. Mehanna and El-Gammal, 2007;Mehanna, 2005Mehanna, to 2020Tesfamichael and Mehanna, 2012;Osman, 2015;Mohamed, 2016;El-Mahdy, 2017;Mehanna et al, 2016Mehanna et al, , 2017Mehanna et al, , 2018Mehanna et al, , 2019Mohamed et al, 2020). In spite of the large area of marine fisheries in Egypt, these fisheries are not exploited rationally due to the decrease of relative abundance of its fish stocks as a result of different reasons such as pollution (domestic and industrial sewages), over fishing and illegal fishing, habitat degradation, human activities on coastal areas, in addition to climate changes.…”
Section: Msy and F Max For Red Sea Fisheriesmentioning
confidence: 99%